Quantification of bioactive constituents of mistletoe leaves (tapinanthus globiferus a. rich) from four different host plants in the EWU community - A. Owolabi, Tunde; O Edobor, Salome (International Journal of Advanced Chemistry, 2022)
Background: Pharmacological activities of the medicinal plant are determined by the chemical substances it contains, these substances are also affected by factors of which geographical and all that surround such plant plays a vital role. Mistletoe is a plant that depends solely on its host. This study evaluated the different phytoconstituents concentrations in Mistletoe (Tapinanthus globiferus) leaves growing on four different host plants (Avocado pear (Persea americana), Orange (Citrus sinensis), Guava (Psidium guajava), and Kolanut (Cola nitida)) in the Ewu community of Edo State, Nigeria.Methods: Qualitative and quantitative phytochemical analyses were carried out using standard methods.Results: The qualitative test revealed the presence of alkaloids, Tannin, Phenolic compounds, Flavonoid, Saponin, while the quantification estimation showed these phytochemicals in varying concentrations. Guava had the highest concentration of Tannin (323.4±0.07), Saponin (138.6 ± 0.02) while Orange has the highest concentration of Flavonoids (632.61 ± 0.12) followed by Guava (407.88 ± 0.05), the highest concentration of Phenolics was found in Avocado pear (519.9 ± 0.29) followed by Guava (273.5 ± 0.34). The highest Alkaloids were found in Orange (2.20 ± 0.06) followed by Avocado pear respectively.Conclusion: From this present study, it can be concluded that Mistletoe from different host plants has a different concentration of phytochemicals and is thus expected to have different bioactivities.